A content analysis on the amplification of President Rodrigo Duterte's war on drugs in Davao newspapers through media reportage - Joaquin, Daniel D.; Glova, Nelfa M. (2018)
This study was conducted to determine whether President Rodrigo Duterte?s war on drugs is amplified or underplayed in stories published on the front page of newspapers published in Davao City. The researcher took sample from Edge Davao, Mindanao Times, and Mindanao Daily Mirror. Slovin?s Formula was used to determine the total sample size of the study. With the use of Statistical Package for the Social Sciences, the researcher was able to determine the frequencies of the publication of certain Duterte-related stories on the front page of each of the 293 issues selected from all three publications. Analysis of the data resulted in the conclusion that the war on drugs is amplified on the front page of Davao newspapers in terms of frequency of publication, but is generally plated down due to the fact that local papers only allocate low amounts of space to the said matter, this is a practical manifestation of Agenda-Setting Theory, which is the underlying theory behind this entire study, as the publications are able to control each subject?s implied level of salience of through the use of newspaper space